Development of Problem Based Learning (PBL) Biology Teaching Modules that Implement the Merdeka Curriculum on Excretion System and Reproductive System Materials - Hesti Julia Permatasari; Setiyo Prajoko; Karunia Galih Permadani (Universitas Tidar, 2023)
In the Independent Curriculum, learning planning can be optimally arranged by creating teaching modules. The purpose of this study was to determine the level of feasibility and teacher responses to teaching modules for teachers on problem-based excretory systems and reproductive systems (PBL) materials based on the Independent Curriculum. This research is a Research and development (R&D) with a 4D model, while the stages carried out are: Define, Design, Develop, and Disseminate. In this research, development was carried out to the develop stage. Data collection techniques using interviews and observation. The instruments used were interview sheets, teaching material expert validation, material expert validation, and teacher response questionnaires. The results of the feasibility of the product that has been developed are in the form of teaching modules from the validation of material experts by 92% and the proportion of teaching material experts by 97.6%. The results of the teacher response test obtained results in the open module of 93.7%. Thus it can be concluded that the teaching modules accompanied by problem-based student modules (PBL) that have been developed are suitable for use by teachers to assist the implementation of learning.